2018
DOI: 10.1371/journal.pone.0188764
|View full text |Cite
|
Sign up to set email alerts
|

Cell type-specific suppression of mechanosensitive genes by audible sound stimulation

Abstract: Audible sound is a ubiquitous environmental factor in nature that transmits oscillatory compressional pressure through the substances. To investigate the property of the sound as a mechanical stimulus for cells, an experimental system was set up using 94.0 dB sound which transmits approximately 10 mPa pressure to the cultured cells. Based on research on mechanotransduction and ultrasound effects on cells, gene responses to the audible sound stimulation were analyzed by varying several sound parameters: frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 53 publications
2
30
0
Order By: Relevance
“…In addition, there were best sound frequencies for the regulation of gene expression related to ethylene biosynthesis of tomato and ascorbic acid biosynthesis of alfalfa sprout vegetable . Moreover, a recent report suggested that four different types of cells when treated with the same sound wave condition responded differently and the expression of related genes also differed . Therefore, because the growth, development and morphology are different in plants, it is estimated that the expression of related genes for a particular sound wave will change differently.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there were best sound frequencies for the regulation of gene expression related to ethylene biosynthesis of tomato and ascorbic acid biosynthesis of alfalfa sprout vegetable . Moreover, a recent report suggested that four different types of cells when treated with the same sound wave condition responded differently and the expression of related genes also differed . Therefore, because the growth, development and morphology are different in plants, it is estimated that the expression of related genes for a particular sound wave will change differently.…”
Section: Resultsmentioning
confidence: 99%
“…For medium and large bubbles, these decreased significantly for SP when sonicated (SPS), increased for Ice with sonication (IceS), but no significant difference was found for Nu and NuS. The changes in bubble size distribution may be due to the effect of the pressure caused by the sonication treatment in the bottle due to the energy associated with the wavelength of audible sound waves, which although lower than ultrasound energy, it still alters the media and particles [25,26]. When the pressure in carbonated beverages is higher, the CO 2 solubility increases [27].…”
Section: Physicochemical Properties Of Carbonated Watermentioning
confidence: 99%
“…This effect has been described in other studies where it was found that higher pressure generates oxidative stress 21 but only cells during the exponential phase are affected. 22,23 It is likely that this response is due to activation of stress-dependent mechanoreceptors 10,20 but possibly only when surpassing a specific high threshold since the response did not appear in the rest of the mild-amplitude treatments.…”
Section: Effect Of Individual Sound Elements Over Biomass Concentratimentioning
confidence: 99%
“…More recently, it has been found that frequency has little biological effect compared with other sound elements. 20 Therefore, the discrepancy between optimal conditions and the non-linearity of frequency effect suggests that it is necessary to perform a broad frequency screening as wide as possible.…”
Section: Effect Of Frequency On Biomass Concentration and Protein Promentioning
confidence: 99%